Research on inlet structure optimisation and numerical simulation of three-phase separator. (31st January 2022) - Liu, Guorong
Three-phase separators are increasingly used in fields such as the pretreatment of oilfield produced fluids and the treatment of oily sewage in the chemical production process. As the core component of the three-phase separator, the inlet structure can make the relatively stable flow field obtained by the separator provide strong guarantee for subsequent separation. An advanced design of inlet structure can improve the separation effect of the separator to a certain extent. In this paper, the Fluent software was used to numerically simulate the inlet structure of the three-phase separator. Through the analysis of different types of inlet structures, the general rules were summarised. Finally, combined with related research results, a bottom cylindrical inlet structure was developed and designed to improve the rectification performance of the inlet structure and effectively prevent the blocking of the distribution cylinder from occurring.